Factores de riesgo para la ocurrencia de Mastitis bovina en Dos Fincas con Diferentes Condiciones Climáticas. (2023)
The objective of the present study is to evaluate the risk factors for the presentation of bovine, clinical and subclinical mastitis in two farms with different climatic conditions, for which a survey was elaborated in relation to the milking routine that is carried out in each one of the properties and thus determine the prevalence, incidence and factors associated with the presentation of mastitis. Evidencing that there is a correlation between the management of milking and the quality of hygiene. The research that has been carried out is of a cross-sectional descriptive type, aimed at animal welfare and health. Based on the information provided by the milkers of each farm, the possible causes for the presentation of mastitis were established. On farm #1, when cleaning the udder, they used a towel, which was shared and used in the 10 cows in production without previous disinfection of this material, additionally they did not have all the milking elements. In farm #2 it was evident that they did not wash and disinfect their hands before and after the activity, as well as an adequate cleaning of the teats, since the milkers used a sheet of paper for every two quarters, which It lends itself to infecting a healthy room if it is used in a sick room of the animal, when the correct thing would be to use one piece of paper for each room. This is undoubtedly a predisposing factor for the transmission of the disease, as well as not performing dry cow treatment predisposes to the presentation of mastitis. This is why we can conclude that bovine mastitis is a big problem for production when adequate measures are not taken, such as regular sampling and the use of effective treatments, based on previous studies of the pathogens that cause the disease and that the best The choice will always be the prevention and management of good milking practices, involving hygienic measures from the moment the animal enters the milking parlor and until it leaves it, this allows 13 13 to considerably reduce the microbial contamination of milk, increase production , shorten milking time and reduce the transmission of contagious and environmental pathogenic organisms that can cause mastitis